Soil Physical Characteristics of The Mangrove Ecosystem in Bone Bay, Palopo City - Ayu, Srida Mitra; Najib, Nardy Noerman; Yumna, Yumna; Witno, Witno; Maria, Maria; Liana, Liana; Sada, Novi Herman; Pitra, Pitra (PLANTA TROPIKA, 2023)
The distribution of mangrove plants is influenced by various factors, including the physical characteristics of the soil. The study was conducted to determine the physical characteristics of the soil in the mangrove ecosystem in Bone Bay, Palopo City. Soil sampling was performed using the purposive sampling method in five points with three replications based on the equations of growth and density of mangrove vegetation. Physical characteristics of the soil sample, including texture, color, permeability, bulk density, and soil porosity, were analyzed in the laboratory. The results showed that the dominant soil textures were squirming and sandy loam. The dominant soil color was very dark gray. Soil permeability is high and belongs to the fast criteria, with the highest value of 20.0 cm/hour at the fourth depth point of 0-30. The highest bulk density at the fourth depth point is 31-60 cm, with a value of 0.81 gr/cm3. At the same time, the porosity of the soil is classified as a high or good criterion, with the highest value found at the third depth point of 0-30 cm with a value of 77%. In the future, soil physical characteristics data can be used as preliminary information or databases for the government to organize and preserve mangrove forests.